Analysis of microplastic content in sediments of two garden ponds located in the Mulawarman University Campus (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Plastic waste is the type of waste that is most commonly found in our environment. Plastic waste that decomposes and degrades into smaller particles is called microplastic. Small-sized microplastics (
Keywords: fiber; fragmens; film; abudance